Validation of an automated assay for the measurement of cupric reducing antioxidant capacity in serum of dogs. Issue 1 (December 2016) - Rubio, Camila; Tvarijonaviciute, Asta; Martinez-Subiela, Silvia; Hernández-Ruiz, Josefa; Cerón, José
Abstract Background The objective of the present study was to optimize and validate an automated method to assess the total antioxidant capacity (TAC) in serum of dogs using the cupric reducing antioxidant capacity (CUPRAC) methodology (TACc ) with bathocuproinedisulfonic acid disodium salt as chelating agent, evaluating also possible variations due to the use of two different automated analyzers. The method is based on the reduction of Cu2+ into Cu1+ by the action of the non-enzymatic antioxidants that are present in the sample. Results Imprecision was low in both apparatus utilized, and the results were linear across serial Trolox and canine serum samples dilutions. Lipids did not interfere with the assay; however, hemolysis increased the TACc concentrations. When TACc concentrations were determined in ten healthy (control) dogs and in twelve dogs with inflammatory bowel disease (IBD), dogs with IBD had lower TACc concentrations when compared with the healthy dogs. Conclusions The method validated in this paper is precise, simple, and fast and can be easily adapted to automated analyzers.